2011
DOI: 10.1371/journal.pone.0017580
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing Negative Soil Biota Effect and No Evidence for Local Adaptation in a Widespread Eurasian Grass

Abstract: BackgroundSoil biota effects are increasingly accepted as an important driver of the abundance and distribution of plants. While biogeographical studies on alien invasive plant species have indicated coevolution with soil biota in their native distribution range, it is unknown whether adaptation to soil biota varies among populations within the native distribution range. The question of local adaptation between plants and their soil biota has important implications for conservation of biodiversity and may just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
1
9
1
Order By: Relevance
“…The absence of local adaptation has also been reported in other plant species, such as Carlina vulgaris [32], Crotalaria pallida [33], Stipa capillata [34] and Helleborus foetidus [35]. Each of these studies provided different explanations for the lack of local adaptation.…”
Section: Discussionmentioning
confidence: 79%
“…The absence of local adaptation has also been reported in other plant species, such as Carlina vulgaris [32], Crotalaria pallida [33], Stipa capillata [34] and Helleborus foetidus [35]. Each of these studies provided different explanations for the lack of local adaptation.…”
Section: Discussionmentioning
confidence: 79%
“…(2010) observed plant local adaptation to soils that differed in microbial structure and soil effects on the heritability of plant traits. By contrast, Wagner et al. (2011) found no evidence that plant populations were locally adapted to soil biota.…”
Section: Discussionmentioning
confidence: 80%
“…Although few studies have investigated evolutionary interactions between plants and their total below-ground community, Pregitzer et al (2010) observed plant local adaptation to soils that differed in microbial structure and soil effects on the heritability of plant traits. By contrast, Wagner et al (2011) found no evidence that plant populations were locally adapted to soil biota. In more tightly linked, pairwise symbiotic relationships, microbially mediated adaptive changes 222 Research New Phytologist have been documented for a wide variety of systems from aphids and their Buchnera endosymbionts (Zilber-Rosenberg & Rosenberg, 2008) to plants and their mycorrhiza mutualists (Johnson et al, 2010).…”
Section: The Relative Importance Of Biotic Vs Abiotic Factorsmentioning
confidence: 80%
“…For instance, other plant-AMF interactions are conceivable with other pairings of AMF communities (species and genotypes), plant genotypes (e.g., Klironomos, 2003;Stahl & Smith, 1984), and growth conditions. Additional experiments that incorporate population and genotypic variability are necessary to quantify general effects of soil microbes across a plant's range (Callaway, Bedmar, Reinhart, Silvan, & Klironomos, 2011;Reinhart, Royo, van der Putten, & Clay, 2005;Wagner, Antunes, Ristow, Lechner, & Hensen, 2011).…”
Section: Discussionmentioning
confidence: 99%